Pengaruh citra merek (brand image) terhadap loyalitas konsumen bakso bakar Pak Man Kota Malang - Qauman Nur Syoalehat; Siti Azizah; Anie Eka Kusumastuti (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
This research was conducted in Bakso Bakar Pak Man from 7th March to 5th April 2016 through a survey method guided by a structured questionnaire. The respondents were selected using accidental sampling technique. The multiple linear regression analysis was used to analyse the data. The results showed that the characteristics of consumer were dominated by female students aged from 17-22 years old, lived in Malang and had monthly income > IDR. 2,000,000. Mostly, they got information about Bakso Bakar Pak Man from their families and friends. The brand image variables (corporate image, user image and product image) simultaneously influenced the consumers’ loyality of “bakso bakar Pak Man”. It can be concluded that brand image variable which consisted of corporate image, user image and product image had a  positive influence to the consumers’ loyality of Bakso Bakar Pak Man. The most influential variable to “bakso bakar Pak Man”consumer’s loyality was corporate image. It is recommended to “bakso bakar Pak Man” to maintain their service quality and product variant for increasing the consumer’s interest and be acquainted with other media. The employee performance, product quality and facilities have to be improved in order to maintain the positive brand image of Bakso Bakar Pak Man. Keywords: corporate image, user image, product image, consumer loyality